Early Detection of Preeclampsia Through Urine Protein Examination as a Means of Maternal Emergency Prevention - Zulfia Samiun; Nasriani Nasriani; Muhammad Purqan Nur; Wulandari Dwi Putri; Nur Ilah (Sarana Ilmu Indonesia (salnesia), 2023)
A decrease in urine albumin levels in pregnant women, which can be checked through urine protein examination, is an indicator used to determine whether a pregnant woman is experiencing preeclampsia. Preeclampsia has become a cause of increasing morbidity and mortality rates which affects both mothers and newborns. This research aimed to early detect the preeclampsia through urine protein examination and see the correlation between the characteristics of the research subjects and urine protein. Used a descriptive design with a correlational design, the urine protein from 36 pregnant women was examined in their second and third trimesters of pregnancy. Next, univariate analysis was carried out and Spearman Correlation test was used in bivariate analysis for abnormally distributed ordinal data while the Contingency Coefficient Correlation test was carried out for data that used abnormally distributed nominal scale. Based on the bivariate analysis, the variables of age, education, employment, and obstetric history obtained a significant value of p value>0,05, showed no correlation with urine protein. Contrarily, the blood pressure variable had a significant value of p 0,049 < 0,05. Pregnant women in gestational age of >20 weeks with high blood pressure must examine the urine protein immediately to early detect preeclampsia and prevent maternal emergencies.